Evaluation of The Program to Improve Understanding of Citizens' Constitutional Rights for Teachers at Pancasila and Constitutional Education Center (Evaluation of The Countenance Stake Model) - Gardina, Angga Putri; Rubini, Bibin; Suhardi, Eka (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
This study aims to describe and analyze the implementation of a program to increase the understanding of citizens' constitutional rights for teachers in Pancasila and Constitutional Education Center. This evaluation study uses the evaluation model developed by Stake, namely the Stake Count model which consists of 3 stages of evaluation: 1) antecedent, 2) transaction, and 3) outcome. The results of research on the antecedent component of the eight aspects of the assessment, there are two aspects in the category of good value, namely the formulation of goals and infrastructure aspects. From the transaction component, all four aspects are categorized as very good. Meanwhile, the outcomes component consists of one aspect, namely the result of the implementation of learning and is in the sufficient category. Based on the thirteen evaluation aspects of the antecedent, transaction, and outcome components, it can be concluded that the program to increase the understanding of citizens' constitutional rights for teachers at Pancasila and Constitutional Education Center has gone well and can be continued with improvements in three aspects, namely the antecedent component on the aspect of goal formulation. and infrastructure as well as outcome components on the expected outcome aspects.